The imposter phenomenon in psychiatrists: relationships among compassion fatigue, burnout, and maladaptive perfectionism - Nur Nihal Türkel; Ahmet Selim Başaran; Hande Gazey; İrem Ekmekçi Ertek (BMC Psychiatry)
Abstract Background The imposter phenomenon is the unwillingness to acknowledge one’s triumphs, which is common among doctors. Research on the imposter phenomenon among mental health professionals is limited, and the relationship between imposter phenomenon, burnout, and compassion fatigue has not been studied. The current study intended to test a hypothesized model of the specific impact paths among burnout, compassion fatigue, maladaptive perfectionism, and imposter phenomenon among mental health professionals. Methods A descriptive, cross-sectional online survey was conducted from June 2023 to September 2023. The sample (n = 160) consisted of psychiatrists. A path analysis was used to test the relationships among study variables and assess model fit. Results A strong correlation was found between the imposter phenomenon and burnout and compassion fatigue when controlling age and months of work for both genders. Maladaptive perfectionism, directly and indirectly, affected the imposter phenomenon through burnout and compassion fatigue. Conclusion This study found that burnout and maladaptive perfectionism impact the imposter phenomenon in psychiatrists. To mitigate the effects of the imposter phenomenon on mental health professionals, societal norms that contribute to burnout and perfectionism must be reassessed.